EXPERIMENTAL STUDY OF BRUSH BORDER REMODELING OF ENTEROCYTES UNDER CHRONIC TOXIC-METABOLIC EXPOSURE - Azimova Masuda Karimovna, PhD (Western European Studies, 2026)
Chronic exposure to toxic agents combined with metabolic disorders represents a significant pathogenic factor affecting the gastrointestinal tract. The small intestine, as a central component of the barrier–metabolic system, is particularly vulnerable to combined toxic–metabolic injury. Structural integrity of the enterocyte brush border plays a crucial role in maintaining effective membrane digestion and nutrient absorption.
Keywords: Brush border; enterocytes; microvilli; chronic intoxication